Adversity for sale : you gotta believe - Jeezy, 1977-; Meadows-Ingram, Benjamin (Harper Collins Leadership, an imprint of HarperCollins, 2023)
To Jeezy's legion of fans, his name is synonymous with hustle, grit, and the integrity to go out there and achieve your dreams. In his first book, Jeezy shares never heard stories of what it took for him to beat the odds and get out of the streets, his mindset he carefully honed to get an edge, and the lessons that changed his life and business.